Physical ecology of hypolithic communities in the central Namib Desert: The role of fog, rain, rock habitat, and light. Issue 4 (24th October 2013) - Warren‐Rhodes, Kimberley A.; McKay, Christopher P.; Boyle, Linda Ng; Wing, Michael R.; Kiekebusch, Elsita M.; Cowan, Don A.; Stomeo, Francesca; Pointing, Stephen B.; Kaseke, Kudzai F.; Eckardt, Frank; Henschel, Joh R.; Anisfeld, Ari; et al.
Abstract [1] Hypolithic microbial communities are productive niches in deserts worldwide, but many facets of their basic ecology remain unknown. The Namib Desert is an important site for hypolith study because it has abundant quartz rocks suitable for colonization and extends west to east across a transition from fog‐ to rain‐dominated moisture sources. We show that fog sustains and impacts hypolithic ecology in several ways, as follows: (1) fog effectively replaces rainfall in the western zone of the central Namib to enable high (≥95%) hypolithic abundance at landscape (1–10 km) and larger scales; and (2) high water availability, through fog (western zone) and/or rainfall (eastern zone), results in smaller size‐class rocks being colonized (mean 6.3 ± 1.2 cm) at higher proportions (e.g., 98% versus approximately 3%) than in previously studied hyperarid deserts. We measured 0.1% of incident sunlight as the lower limit for hypolithic growth on quartz rocks in the Namib and found that uncolonized ventral rock surfaces were limited by light rather than moisture. In situ monitoring showed that although rainfall supplied more liquid water (36 h) per event than fog (mean 4 h), on an equivalent annual basis, fog provided nearly twice as much liquid water as rainfall to the hypolithic zone. Hypolithic abundance reaches 100% at a mean annual precipitation (MAP) of approximately 40–60 mm, but at a much lower MAP (approximately 25 mm) when moisture from fog is available.